PS4:72 Antiphospholipid antibodies and autoimmune hemolitic anaemia in systemic lupus erythematosus: a case-control study. (21st March 2018) - Crisafulli, F; Andreoli, L; Franceschini, F; Frassi, M; Fredi, M; Nalli, C; Tincani, A
Abstract : Purpose: Hemolitic anaemia with reticulocitosis is included in ACR and SLICC classification criteria of Systemic Lupus Erithematosus (SLE). Some studies have assessed the relationship between antiphospholipid antibodies (aPL) and autoimmune hemolitic anaemia (AIHA) in SLE patients. Some of them had describe a correlation with the presence of Lupus anticoagulant (LAC) as other highlighted the association with a positive anti-B2glycoprotein I (B2GPI) IgG or anti-cardiolipin (aCL) IgM. The purpose of our preliminary study is to analyse and compare aPL positivity in two groups of SLE patients, one with a history of AIHA and one without it. Methods: The retrospective analysis of our cohort of 514 SLE patients showed that 16 subjects fulfil a completely documented diagnosis of AIHA at some stage of their disease. These subjects and 32 consecutive SLE patients without any haematological manifestations were included in this study. Clinical and serological data were obtained from medical records of our clinic. We compared the prevalence of aPL, their type (aCL IgG and IgM, B2GPI IgG and IgM, LAC) and titre using Fisher exact test in the two groups of patients. Results: Lupus patients with AIHA had a significantly higher frequency of aPL positivity compared with SLE patients without AIHA (81% vs 44%, p value=0, 0164). Furthermore, double aPL positivity was detected in 53% of patients with AIHA as in the control group was 22% (p value=0, 0459). The positivity of aCL and B2GPI was higher in the group of patients with history of AIHA than in the control group (39% vs 25% and 63% vs 41%, respectively) but the difference was not statistically significant; table1 details the results of each antibody isotype and titres. The presence of LAC was significantly associated with history of AIHA (p value=0, 0131). Conclusions: In this control-case study the frequency of aPL was higher in SLE patients with a history of AIHA. In particular, in this group we found a higher frequency of double aPL positivity. Between aPL, LAC had the strongest association with AIHA. The absence of statistical difference considering aCL and B2GPI positivity and titres could be due to the low sample size.